"Biggest Nationalist in the Country": Self-Descriptive Uses of "Nationalist" in Contemporary Russia. Issue 2 (1st December 2021) - Laine, Veera
Abstract: Nationalism is an ism rarely used as self-description. This article suggests that nationalist discourses are on the move, meaning the concept may be used in novel ways. In Russia, for example, the president recently identified himself as a nationalist, claiming ownership of the concept in the long-standing struggle against manifestations of oppositional nationalism. The article asks who describes themselves as nationalists in contemporary Russia, how do they define the concept, and how did it change during the years 2008–2018 when nationalism as a political idea became increasingly important in Russian politics? Drawing from Russian newspaper sources, the article suggests that diverse, self-proclaimed nationalist actors rely on narrow ethnic understandings of the concept and do not embrace the president's interpretation of multinational nationalism.